PENGARUH PENDAPATAN ASLI DAERAH, DANA PERIMBANGAN, BELANJA MODAL TERHADAP KINERJA KEUANGAN PEMERINTAH DAERAH DI KABUPATEN KEPULAUAN TANIMBAR - Silvy Theovilia Refialy; Linda Grace Loupatty (ADISAM PUBLISHER, 2025)
This research aims to test and analyze the influence of local revenue, balancing funds and capital expenditure on the financial performance of the Tanimbar Islands Regency regional government. The research was conducted at the Tanimbar Islands Regency Regional Government office in Saumlaki City and the Maluku Provincial Inspectorate office in Ambon City. This research is quantitative research using secondary data in the form of budget realization data for the Regional Government of the Tanimbar Islands Regency, which was obtained from the Secretariat of the Regent of the Tanimbar Islands Regency and the Maluku Provincial Inspectorate. The data analysis method uses the Multiple Linear Regression statistical test. The research results show that local original income has a significant positive influence on the financial performance of the Tanimbar Islands Regency Regional Government. Balancing funds and capital expenditures have an insignificant positive influence on the financial performance of the Tanimbar Islands Regency regional government